2011
DOI: 10.7326/0003-4819-155-1-201107050-00005
|View full text |Cite
|
Sign up to set email alerts
|

Is Pocket Mobile Echocardiography the Next-Generation Stethoscope? A Cross-sectional Comparison of Rapidly Acquired Images With Standard Transthoracic Echocardiography

Abstract: BACKGROUND A new miniature high-resolution pocket-mobile echocardiographic (PME) device has become available to clinicians, but there are no data available comparing this technology with standard transthoracic echo (TTE) examination. OBJECTIVE To assess the potential validity of PME imaging as a quick assessment of cardiovascular disease by direct comparison to standard TTE. DESIGN Ultrasonographers attempted to acquire seven standard echocardiography views with the PME prior to performing comprehensive st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
96
0
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(110 citation statements)
references
References 9 publications
5
96
0
6
Order By: Relevance
“…Although this study commented on the accuracy of PSE compared to sTTE in a subset of patients, this was not the primary objective. Image accuracy has been previously well described in various other patient populations [7][8][9][10][11][12][13][14][15][16][17][18]. Finally, although this study validated the use of PSE in assessing LVEF, if more extensive information on cardiac structure and function is required clinically prior to PPM implantation sTTE is superior to that of PSE.…”
Section: Limitations and Future Directionsmentioning
confidence: 51%
See 2 more Smart Citations
“…Although this study commented on the accuracy of PSE compared to sTTE in a subset of patients, this was not the primary objective. Image accuracy has been previously well described in various other patient populations [7][8][9][10][11][12][13][14][15][16][17][18]. Finally, although this study validated the use of PSE in assessing LVEF, if more extensive information on cardiac structure and function is required clinically prior to PPM implantation sTTE is superior to that of PSE.…”
Section: Limitations and Future Directionsmentioning
confidence: 51%
“…The use of the PSE to visualize left ventricular wall motion and systolic function has been previously evaluated. Several studies have demonstrated that the PSE can obtain interpretable images in the vast majority (85-100%) of patients by inexperienced sonographers, in both the inpatient and outpatient settings [10][11][12]. A complete sTTE study takes approximately 20-25 minutes to acquire, with a standard echocardiography machine costing approximately four times that of a PSE machine [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pocket-sized ultrasound devices are powerful tools that have been found to perform similarly to traditional high-end systems when used by experienced clinicians. [5][6][7][8][9][10][11][12][13] Internal medicine residents desire ultrasound training, but self-reported competence is low. 14 Several studies have shown that after brief training, residents can become competent in performing and interpreting basic ultrasound examinations.…”
Section: Introductionmentioning
confidence: 99%
“…Moving to a very different clinical setting, a current cross sectional study by Liebo et al comparing echocardiograms taken by a 'pocket mobile device' (VScan GE® Healthcare, Milwaukee) ( Figure 2) and a standard trans-thoracic echocardiogram (TTE) demonstrated highly correlative findings in most cardiac function measurements. 5 Within the constraints of a single centre study, they found that pocket mobile echocardiography (PME) yielded accurate assessments of ejection fraction and cardiac function, however there was a variance in accuracy with mitral valve abnormalities and inferior vena cava size. Interestingly, a similar comparison study using a different pocket echocardiograph (Acuson P10, Siemens®, Mountain View, CA) showed that there was a good correlation with standard TTE to quantify ejection fraction.…”
mentioning
confidence: 99%